Chemical Pulps for Writing and Printing Papers from Cymbopogon winterianus Jowitt (Java Citronella Grass) - Guha, S. R. D.; Pant, Rajesh; Karira, B. G. (Indian Forester, 1974)
Laboratory experiments on the production of chemical pulps for writing and printing papers by soda process from unextracted and extracted Cymbopogon winterianus Jowitt, (Java citronella grass) are described. The average fibre length was 0.98 mm and the everage fibre diameter was 0.014 mm. Bleached pulps of good strength properties could be prepared from this raw material.